2019
DOI: 10.3747/co.26.4517
|View full text |Cite
|
Sign up to set email alerts
|

Framing of the Opioid Problem in Cancer Pain Management in Canada

Abstract: Two guidelines about opioid use in chronic pain management were published in 2017: the Canadian Guideline for Opioids for Chronic Non-Cancer Pain and the European Pain Federation position paper on appropriate opioid use in chronic pain management. Though the target populations for the guidelines are the same, their recommendations differ depending on their purpose. The intent of the Canadian guideline is to reduce the incidence of serious adverse effects. Its goal was therefore to set limits on the use of opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The results of this study showed that foot reflexology has a large effect on pain reduction (d = - It was also reported that foot reflexology enhanced the quality of life, and decreased anxiety and pain intensity as well as side effects reduction in stage of metastatic cancer patients [18,32,33]. It can deduced a conclusion from the enhanced psychological wellbeing and reduced muscle tension, caused by blood redistribution to the target organ [30,31,33].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The results of this study showed that foot reflexology has a large effect on pain reduction (d = - It was also reported that foot reflexology enhanced the quality of life, and decreased anxiety and pain intensity as well as side effects reduction in stage of metastatic cancer patients [18,32,33]. It can deduced a conclusion from the enhanced psychological wellbeing and reduced muscle tension, caused by blood redistribution to the target organ [30,31,33].…”
Section: Discussionmentioning
confidence: 55%
“…The prevalence of sleep disorder was shown to be twofold higher in cancer patients than in the general population [27], and was shown to be associated with pain and depression, poor quality of life, immune dysfunction, decreased cognitive function, and increased mortality [28,29,30]. As the results of the present study confirmed that foot reflexology has a large effect on sleep, it is necessary to apply foot reflexology that is non-invasive and that has a systemic relaxation effect to enhance sleep in the future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is affects approximately 66% cancer patients [43], distressing or intolerable in more than one-third of patients [44] and chronic pain is associated with primary cancer itself or metastases or its treatment (chronic post-cancer treatment pain) [43][44][45][46]. Although, WHO described opioids as essential medicines for pain control but distribution shows substantial inequity, a less than 20% of the world's population consuming more than 90% of the world's supply [46]. Also, some 85% of PCPs perceived their training in pain management to be inadequate in a Pan-European survey [47].…”
Section: Reasons Behind Choosing Alternative Carementioning
confidence: 99%
“…Also, some 85% of PCPs perceived their training in pain management to be inadequate in a Pan-European survey [47]. Along with these, fear of dependence, prescription diversion, regulatory scrutiny, withdrawal symptoms, opioid-related adverse events and deaths limit its use [46], [48][49][50][51][52]. There is a lack of high-quality evidence regarding the analgesic efficacy of NSAIDs in cancer; contradiction and inconsistent findings also reported [53,54], although advocated as a useful adjunct for management of cancer pain [55,56].…”
Section: Reasons Behind Choosing Alternative Carementioning
confidence: 99%
“… 23 Thus, several regions, particularly in North America, have seen increased scrutiny and regulation over opioid prescribing—even for cancer-related pain. 1 , 11 , 27 These issues have had an impact on the delivery of pain management to patients suffering from cancer-related pain and—in addition to finding more effective pain therapies as well as minimizing opioid-related problems—have also emphasized the need to develop new nonopioid pain treatment strategies. 31 …”
Section: Introductionmentioning
confidence: 99%